Studi Komparasi Hukum Jual Beli Penggunaan Uang Muka Menurut Empat Imam Madzhab - Arifin, Desi Siti Habibah; Nuraeni, Neni; Januri, Fauzan (Jurnal Iqtisad, 2024)
Down payment is called urbun in Fiqh studies. There are differences of opinion regarding the legal status of the use of the down payment or urbun. This research is a type of qualitative literature research with descriptive analysis method. Data sources come from written literature, such as books, books, scientific articles, and others related to the subject of research. The Hanafi and Shafi'i Madzhab tend not to allow it because it is considered to contain elements of uncertainty and potential injustice, while the Maliki and Hanbali Madzhab tend to allow this practice on condition that there is a clear agreement, which later became the basis for the issuance of DSN-MUI Fatwa No. 13/DSN-MUI/2000 concerning Down Payment in Murabahah.Â